Public health risk of antimicrobial resistance transfer from companion animals. (5th December 2016) - Pomba, Constança; Rantala, Merja; Greko, Christina; Baptiste, Keith Edward; Catry, Boudewijn; van Duijkeren, Engeline; Mateus, Ana; Moreno, Miguel A.; Pyörälä, Satu; Ružauskas, Modestas; Sanders, Pascal; Teale, Christopher; et al.
Abstract : Antimicrobials are important tools for the therapy of infectious bacterial diseases in companion animals. Loss of efficacy of antimicrobial substances can seriously compromise animal health and welfare. A need for the development of new antimicrobials for the therapy of multiresistant infections, particularly those caused by Gram-negative bacteria, has been acknowledged in human medicine and a future corresponding need in veterinary medicine is expected. A unique aspect related to antimicrobial resistance and risk of resistance transfer in companion animals is their close contact with humans. This creates opportunities for interspecies transmission of resistant bacteria. Yet, the current knowledge of this field is limited and no risk assessment is performed when approving new veterinary antimicrobials. The objective of this review is to summarize the current knowledge on the use and indications for antimicrobials in companion animals, drug-resistant bacteria of concern among companion animals, risk factors for colonization of companion animals with resistant bacteria and transmission of antimicrobial resistance (bacteria and/or resistance determinants) between animals and humans. The major antimicrobial resistance microbiological hazards originating from companion animals that directly or indirectly may cause adverse health effects in humans are MRSA, methicillin-resistant Staphylococcus pseudintermedius, VRE, ESBL- or carbapenemase-producing Enterobacteriaceae and Gram-negative bacteria. In the face of the previously recognized microbiological hazards, a risk assessment tool could be applied in applications for marketing authorization for medicinal products for companion animals. This would allow the approval of new veterinary medicinal antimicrobials for which risk levels are estimated as acceptable for public health.